Dialogues of knowledge and horizontal research in the social appropriation of knowledge in CTeI (Encuentros, 2025)
The article presents an epistemological, theoretical, and methodological reflection from research on the social appropriation of knowledge in CTeI with young people and women from southwest Antioquia in Colombia. The methodology is horizontal research and dialogue on knowledge to contribute to developing a scientific culture in six territories of the San Juan Basin. Share and build computer knowledge, programming, science, technology, and innovation. Fieldwork carried through citizen participation and collaborative thinking through training workshops, photo ethnography, and videos. The findings show differences in the appropriation of scientific and technological knowledge. CTeI achieved more openness among women and young people. It has concluded that it is important to continue strengthening the situated scientific culture.
Keywords: Social appropriation of knowledge; Dialogue of Knowledge; Horizontal Research